Analysis of water reuse systems in offshore oil platform - Mui, Taiana She Mir [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
Water is a necessary asset in the daily life of all living beings, however, it is a finite asset and in some regions of the planet it has already become scarce. Offshore oil and gas extraction platforms have a voluminous water cycle. Produced water is considered the largest by-product of the oil extraction process, for each barrel of oil obtained about 3 to 5 barrels of produced water are also extracted. For the produced water to be disposed or reused it is necessary to go through a series of previous treatments before being reapplied or released into the environment, each country has its own legislation and regulatory agencies responsible for the quality of this water. This work aims to provide an overview of the water cycle inside offshore platforms from its acquisition, treatment, reuse and final disposal. In addition, a case study about four platforms of Petrobras company will be presented to show how the management of water and effluents are done inside these platforms. In conclusion, the water cycle inside offshore platform is complex because it involves different types of water (potable, produced, reuse and waste), several logistics and engineering processes for the treatment, reapplication and subsequently disposal of the water. In Petrobras platforms, potable water was obtained by both ways via transportation and desalination. Another important finding was that in Petrobras semi-submersible platforms, there was not available a treatment system for effluents or produced water. The reason why the percentage of produced water reuse is small and not always viable is due to the costs of treatment, transportation and storage of the water

Á água é um bem necessário no dia a dia de todos os seres vivos, porém é um bem findável, tanto que em algumas regiões do planeta já tem se tornado escasso. Plataformas offshore de extração de óleo e gás possuem um volumoso ciclo de água. A água produzida é considerada o maior subproduto do processo de extração de petróleo, para cada barril de óleo são extraídos também cerca de 3 a 5 barris de água produzida. Para a água produzida ser descartada ou reutilizada é necessário passar por uma série de tratamentos prévios antes de serem reaplicadas ou lançadas no ambiente, cada país possui suas legislações e órgão regulamentadores responsáveis pela qualidade dessa água. Este trabalho visa fornecer uma visão geral do ciclo da água dentro de plataformas offshore desde a sua aquisição, tratamento, reutilização e descarte final. Além disso, um estudo de caso de quatro plataformas da empresa Petrobras será apresentado com a finalidade de mostrar como é a gestão da água e efluentes dentro de plataformas. Em conclusão, o ciclo da água dentro da plataforma offshore é complexo porque envolve diferentes tipos de água (potável, produzida, reutilizada e residual), vários processos logísticos e de engenharia para o tratamento, reaplicação e subsequente eliminação da água. Nas quatro plataformas da Petrobras estudadas, a água potável tem sido obtida por ambos os métodos: via transporte e por dessalinização. Outra descoberta importante foi que nas plataformas semissubmersíveis não existiam um sistema de tratamento de efluentes ou de água produzida. A razão pela qual a percentagem de reutilização da água produzida é pequena e nem sempre viável, deve-se aos custos de tratamento, transporte e armazenamento da água.
Análise de sistemas de reutilização de água em plataformas petrolíferas offshore
Keywords: Offshore; Water; Produced Water; Reuse; Água; Agua produzida; Reúso; Água - Estações de tratamento; Engenharia de abastecimento; Água - Qualidade